From Influence to Intention: The Power of Celebrity Endorsers and Consumer Perception in Skincare Purchases - Abdallah, Ulil Albab; Moko, Wahdiyat (Jurnal Manajemen Pemasaran dan Perilaku Konsumen, 2025)
This study aims to examine the influence of celebrity endorsers and consumer perceptions on purchasing decisions in the cosmetics industry, specifically focusing on Wardah products. The research adopts an explanatory design to test the relationships among the proposed variables. Data were collected from Generation Z consumers who have previously purchased Wardah products through a questionnaire using a Likert scale. Multiple linear regression analysis was employed to test the hypotheses. The findings reveal that both celebrity endorsers and consumer perceptions have a positive and significant effecton purchasing decisions, both simultaneously and partially. Celebrity endorsement strengthens brand appeal and consumer trust, while favorable consumer perceptions enhance purchase confidence and loyalty.